Preparedness and Mitigation Measures for Oil and Gas Pipeline Vandalization in the Niger Delta Region of Nigeria - Emelu, V. O.; Eludoyin, O. S.; Oyegun, C. U. (Environmental Management and Sustainable Development, 2021)
Owing to poor preparedness and mitigation measures for oil and gas pipeline vandalization in the Niger Delta Region of Nigeria, there have been series of spills that have now reached life threatening levels. This study set out to investigate factors that affect preparedness and mitigation measures for crude oil pipeline vandalism in the study area. The thrust of the study was to unravel the spatial variation in the preparedness and mitigation measures for crude oil pipeline in the region. The study used the survey research method and primary data was sort using questionnaire. The target population were heads of household and workers of multinational companies working in the area. Analysis of variance was used for hypotheses testing at the 0.05 level of significance. The study revealed that the companies’ preparedness options were, use of hazard, risk and vulnerability assessment (76%). Both the community (42%) and companies (76%) respondents averred that the preparedness measure adopted in the area were less effective for combating the menace of pipeline vandalism. The mitigation practices against pipeline vandalization adopted included awareness creation, promoting community participation, community policing, community-based pipeline surveillance, community by laws, right of way, punishment for offenders, and excommunication. Majority of the respondent whether community respondents (48%) or companies respondents (84%) suggested that, the adopted mitigation measures were not effective. The ANOVA model was significant at p<0.05 (F, 14 sig 0.000) meaning that there is statistical significant variation in the level of preparedness for oil and gas pipeline vandalization in the study area. Similarly, the ANOVA model that measured the spatial variation in mitigation measures showed that the model is significant at p<0.05(F, 16.83, sig 0.000), meaning there is statistical significant spatial variation in the level of disaster mitigation for oil and gas pipeline vandalization in the study area. The study recommends improvement in surveillance technology, creation of awareness of the dangers of pipeline vandalism to the locals, amongst others.